Gaondevi temple at Mazagaon hill - Mumbai Archive Project Team (Jio Institute, 2024)
The Gaondevi Temple honours the village deity (Goddess) of Mazagaon. The Koli community worships an imprint of a foot that they believe was left by the Goddess, hoping that it will protect fishermen on the high seas. The current temple is situated on Mazagaon Hill, however, this is not where it was historically located. During Navratri, the temple comes to life as the Gaondevi is ritualistically transported across Mazagon.